2021
DOI: 10.1186/s41687-021-00336-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health-related quality of life in patients with rare disease

Abstract: Background There has been a growing emphasis on health-related quality of life (HRQoL) as an important outcome in rare disease drug development, although its assessment may be useful outside the drug development context, including in clinical applications or natural history studies. Central to assessing quality of life in health research is utilizing outcome measures that capture symptoms and impacts of the disease and treatment that are important and relevant to patients. Identifying and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…PROMs are highly effective for ensuring the patient voice informs best practice care [ 22 , 23 ]. The collection of PROMs by RDRs offers the potential to improve patient care and clinical outcomes [ 21 , 24 ]. Nonetheless, only 40% RDRs reported capturing PROMs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…PROMs are highly effective for ensuring the patient voice informs best practice care [ 22 , 23 ]. The collection of PROMs by RDRs offers the potential to improve patient care and clinical outcomes [ 21 , 24 ]. Nonetheless, only 40% RDRs reported capturing PROMs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the scarcity of valid QoL PROMs and ObsROMs for most rare diseases and the challenges of validating the current available tools, pose a problem to adequately appraise potential treatments. Creative and pragmatic solutions are warranted to overcome difficulties related to small patient cohorts, the cost of tools’ development, and the urgency for making new therapies available [ 4 , 5 ].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Concerning rare diseases, the study of QoL is challenging due to methodological issues as well as to limited literature on those conditions. Small patient populations, disease heterogeneity and scarcity of medical knowledge and specialists hamper the understanding of the burden of these diseases [ 4 , 5 ]. This highlights the importance of ensuring a community-centric approach, including the professionals’ experience and the patients’ voice.…”
Section: Introductionmentioning
confidence: 99%
“…Gathering meaningful data on the HRQoL of people with rare diseases is especially challenging, [41][42][43] and GPP is no exception. Many of the studies identified in this SLR had limitations, including a very small population size and reporting limited data of interest, as they had not been designed with the specific goal of measuring HRQoL in people with GPP.…”
Section: Investigating the Hrqol And Severity Of Symptoms In People W...mentioning
confidence: 99%